FESTIVAL ANAK SHOLEH SEBAGAI MEDIA EDUKASI MODERASI BERAGAMA BAGI GENERASI MUDA DI DESA UNTEMUNGKUR - Ahmad Sharqawi; Abdur Rizki; Muhammad Wahyudi; Dinda Sri Rezeki; Sonia Daulay (Smart Education, 2025)
Abstract: The pious children's festival as a medium for religious moderation education aims to understand and highlight the role of this festival as a means of character education for children, involving the development of interests and talents in the field of Islam. It is a medium for character building, strengthening religious identity, empowering local communities, promoting moral values, and instilling positive habits from an early age. This method is qualitative because it focuses on direct observation of the phenomena that occur during the festival activities. The data analysis techniques applied include three main stages, namely data reduction and conclusion drawing. The pious children's festival shows that this festival plays an important role as a means of character education for children because it successfully develops children's interests and talents in the field of religion, increases their self-confidence, and fosters motivation to learn Islam. It also strengthens children's religious identity, empowers local communities, and promotes positive habits. The pious children's festival is not only a competition, but also a fun and effective learning medium for nurturing Islamic character and self-confidence from an early age. This short activity will be a direct learning experience that involves various aspects of holistic child development in Untemungkur Village, Kolang District, Central Tapanuli Regency. Keywords: Educational Media, Religious Moderation, Anal Sholeh Festival Abstrak: Festival anak sholeh sebagai media edukasi moderasi bergama bertujuan untuk memahami dan menyalakan peran festival ini sebagai sarana pendidikan karakter anak yang melibatkan pengembangan minat dan bakat dalam bidang agama Islam. Media pembinaan karakter, penguatan identitas keagamaan, pemberdayaan komunitas lokas, promosi nilai moral, dan penanaman kebiasaan positif sejak dini. Pelaksanaan festival anak sholeh adalah metode deskriptif kualitatif. Teknik analisis data yang diterapkan meliputi tiga tahap utama yaitu reduksi data, dan penarikan kesimpulan. Festival anak sholeh menunjukan bahwa festival ini berperan penting sebagai sarana pendidikan karakter bagi anak-anak, karena berhasil mengembangkan minat dan bakat anak dalam bidang agama, meningkatkan rasa percaya diri, serta menumbuhkan motivasi belajar agama Islam dan mampu memperkuat identitas keagamaan anak-anak, memberdayakan komunitas lokal, serta kebiasan positif. Kegiatan festival anak sholeh tidak hanya sebagai kompetensi ajang, tetapi juga sebagai media pembeajaran yang menyenangkan dan efektif untuk menumbuhkan karakter Islam dan rasa percaya disi sejak dini. Kegiatan yang berlangsung singkat akan menjadi pembelajaran langsung yang melibatkan berbagai aspek pengembangan anak secara holistik di Desa Untemungkur, Kecamatan Kolang, Kabupaten Tapanuli Tengah.Kata kunci: Media Edukasi, Moderasi Beragama, Festival Anal Sholeh